CHARACTERISTICS OF ELDERLY OSTEOARTHRITIS PATIENTS AT RSUD DR. H. CHASAN BOESOIRIE - Garini, Hapsari Ardha; Manaf, Abd. Azis; Dahlan, Muh. (Universitas Muhammadiyah Ponorogo, 2024)
Osteoarthritis (OA) is a degenerative joint disease that is still a public health problem, especially among the elderly. This problem is caused by the high prevalence of OA and its chronic and progressive nature. The objective of this study was to determine the characteristics of elderly OA patients at Dr H. Chasan Boesoirie Hospital which is a referral hospital centre. This study is a descriptive study approach to 43 samples of elderly OA patients at Dr. H. Chasan Boesoirie Hospital taken using medical record data with total sampling technique. Of the 43 samples, 86.0% were elderly (60-74 years old), 51.2% were female, 46.5% were housewives, 83.7% were located in the knee joint, 39.5% had a Body Mass Index with obesity category I, and 72.1% had comorbidities. The distribution of OA patients at RSUD. Dr. H. Chasan Boesoirie tends to increase in the elderly group (60-74 years), especially in individuals who are female, and work as housewives. Regarding the location of the affected joints, the most common is found in the knee joint, especially in individuals with BMI category of obesity I. The most common comorbidities found in OA patients in this study were is having more than 1 comorbidity